Lingüística de la experiencia hablante. - Hurtado Valero, P.M. (Didáctica. Lengua y Literatura, 2001)
There is no discontinuity between the linguistie knowledge as a competence that makes possible the act of speech, and the linguistic knowledge as a reflection on the experience of speaking: just the action of speaking can be considered a linguisties ¡a nace. This article shows some examples, and it concludes that the linguistíc selence should not go so far away from the common experience (the experience the ordinary speaker has got about his language).
Keywords: Epistemology experience of speaking; linguistics «in nuce»; language; act of speech